Perancangan Media Pembelajaran Menggunakan Microsoft Sway pada Mata Kuliah Medan Elektromagnetik Di Prodi Pendidikan Teknik Elektronika UNJ - Rivaykusnanto, Afif; Sukardjo, Mochammad; Setyowati, Arum (PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA, 2023)
This study aims to develop Microsoft Sway learning media for the Electromagnetic Field course for students of the Electronic Engineering Education Study Program at Jakarta State University and to test the feasibility level of the media. This study uses the Research and Development (RnD) method with the ADDIE model which includes; Analysis, Design, Development, Implementation, and Evaluation. The results of the development of Microsoft Sway learning media for the Electromagnetic Field course are used for the material of Electric Energy and Potential and Transmission Lines. Based on the feasibility category, it can be concluded that the Microsoft Sway learning media developed for the Electromagnetic Field course can be categorized as very feasible to be used as a learning medium.